Efektivitas Larutan Daun Pepaya ( Carica Papaya) Terhadap Kematian Larva Aedes Aegypti - Gusti Syarif Hidayatullah; Isnawati Isnawati; Muhammad Irfa'i (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2020)
Aedes aegypti mosquito is a type of mosquito that can carry dengue virus which causes dengue fever (DHF). Dengue transmission can be reduced by vector control to reduce the population of Aedes aegypti mosquitoes, namely by reducing larval growth. Eradication can be done by giving environmentally friendly plant larvaside. Plants that have the potential as vegetable larvasides are papaya leaves (Carica papaya).. The type of research used is true experiments. The study design uses an e-simple design (post-test only control group design). The population and sample were 3 Aedes aegypti instar larvae obtained in the Banjarbaru region. With a total of 600 tails. With variations in concentration of 0% (control), 6%, 8%, 10%, 12%, and 14% with 4 repetitions at each concentration. then observed the number of larvae that died for 24 hours.Based on the results of research conducted for 24 hours with papaya leaf larvasidehighest concentration14% / 100 ml of water can kill larvae as much as 96% with an average death of 24 animals. With statistical testsAnova Ona Way is p = 0,000